Indigenous Knowledge Masyarakat Etnis Karo terhadap Pengelolaan Tumbuhan Hutan di Desa Lingga, Kabupaten Karo - Agung Suharyanto; Ramot Simon Hans Kristian Harianja; Putri Wijayanti Ndraha; Ika Santi Kasima Saragih; Karen Fransiska Sipayung; Nurhasanah Harahap; Richard Daniel Nababan (Mahesa Research Center, 2019)
Purpose of this study is to determine the Indigenous Knowledge ethnic Karo to the use of plants Forest and to know the processing plants Forest in the village Lingga as the treatment of traditional. This study using qualitative research methods with descriptive approach. Indigenous Knowledge owned ethnic communities Karo this is hereditary, which is inherited directly from their ancestors. Uniquely although inherited hereditary, not necessarily all family members can have the expertise of this, still only people tertentulah in the family pass on the ability in the manufacturing of traditional medicines this. There are a variety of drugs formulated by ethnic communities Karo of herbs Forest around the village Lingga by using the way, tools and simple ingredients used to be drugs to overcome the different types of disease, ranging from mild disease, such as headache, cough, colds, etc., up to the disease that requires handling serious, such as the wound in the result of an accident. as for the type of drugs is among others: blurted, drugs in or cuts deep parem, fresh, eye drug, drug smallpox, clean skin the newborn, drug wound, keeping the waist baby when learning run, and drug sprained